Strategi Komunikasi Bisnis di TikTok Shop untuk Meningkatkan Penjualan Produk UMKM di Kabupaten Gresik - Mochammad Arkansyah; Arfiyansyah; Yuga Adi Kusuma; Salahudin Al Afgan; Paskalis Dio (LPPM Stikosa-AWS, 2025)
This research aims to analyze the business communication strategies used by Micro, Small and Medium Enterprises (MSMEs) in Gresik Regency through the TikTok Shop platform in an effort to increase sales of their products. TikTok Shop as a social media-based e-commerce platform provides interactive features that allow MSMEs to promote products creatively through short videos. This research uses a qualitative method with a case study approach on several MSMEs in Gresik Regency who actively use TikTok Shop. Data was collected through in-depth interviews with MSME owners and analysis of video content on their TikTok accounts. The research results show that effective communication strategies include creating authentic content, collaborating with local influencers, and utilizing live shopping features to build direct interactions with consumers. Apart from that, optimizing the use of hashtags and the latest trends on TikTok also contributes to increasing product visibility and sales. This research concludes that adopting digital communication strategies that are adaptive to the characteristics of the TikTok Shop platform can help MSMEs in Gresik Regency increase sales of their products. The implications of this research provide guidance for MSMEs and stakeholders in utilizing social media as an effective marketing tool.